Mechanisms of Dexmedetomidine in Neuropathic Pain - Zhao, Yang; He, Jianshuai; Yu, Ning; Jia, Changxin; Wang, Shilei (Frontiers in Neuroscience, 2020)
Dexmedetomidine is a new-generation, highly selective α2 adrenergic receptor agonist with a large number of advantages, including its sedative and analgesic properties, its ability to inhibit sympathetic nerves, its reduced anesthetic dosage, its hemodynamic stability, its mild respiratory depression abilities and its ability to improve postoperative recognition. Its safety and effectiveness, as well as its ability to provide a certain degree of comfort to patients, make it a useful anesthetic adjuvant for a wide range of clinical applications. For example, dexmedetomidine is commonly used in patients undergoing general anesthesia, and it also exerts sedative effects during tracheal intubation or mechanical ventilation in intensive care unit patients. In recent years, with the deepening of clinical research on dexmedetomidine, the drug is still applied in the treatment of spastic pain, myofascial pain, neuropathic pain, complex pain syndrome and chronic headache as well as for multimodal analgesia. However, we must note that the appropriateness of patient and dose selection should be given attention when using this drug; furthermore, patients should be observed for adverse reactions such as hypotension and bradycardia. Therefore, the safety and effectiveness of this drug for long-term use remain to be studied. In addition, basic experimental studies have also found that dexmedetomidine can protect important organs, such as the brain, heart, kidney, liver and lung, through various mechanisms, such as anti-sympathetic effects, the inhibition of apoptosis and oxidative stress and a reduction in the inflammatory response. Moreover, the neuroprotective properties of dexmedetomidine have received the most attention from scholars. Hence, in this review, we mainly focus on the characteristics and clinical applications of dexmedetomidine, especially the role of dexmedetomidine in the nervous system and the use of dexmedetomidine in the relief of neuropathic pain.